Apocalypse bow wow - Proimos, James, III (Bloomsbury, 2016)
After all human disappear into thin air, the animals are left behind. Dog buddies Brownie and Apollo, unable to find their owners, decide to set out in the world to find food and water, and maybe build a new society out of the pets that are left behind.